2011
DOI: 10.23960/j.hptt.181-7
|View full text |Cite
|
Sign up to set email alerts
|

Tanaman Indikator Dan Teknik Rapd-PCR Untuk Penentuan Biotipe Bemisia Tabaci Gennadius (Hemiptera: Aleyrodidae)

Abstract: Indicator Plant and PCR-RAPD for Biotype Determination of Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae).B. tabaci has been known world wide as a major pest and virus vector of horticulture. In Indonesia the presence of B.tabaci was reported since 1980 and its role as virus vector in tomato and chilli pepper has becoming more importantrecently. Genetic diversity of B. tabaci has been well recognized, but very little information available for diversity of B.tabaci in Indonesia. This research was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Several studies have been done to identify genetic characteristics of B. tabaci in Indonesia. Hidayat et al (2008) detected B (MEAM1) dan non-B B. tabaci biotypes by using PCR. Another study analyzed COI sequence and found different native genotypes in Indonesia, including Asia I, Asia II 5, Asia II 6, Asia II 7, Asia II 12, and Australia/Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been done to identify genetic characteristics of B. tabaci in Indonesia. Hidayat et al (2008) detected B (MEAM1) dan non-B B. tabaci biotypes by using PCR. Another study analyzed COI sequence and found different native genotypes in Indonesia, including Asia I, Asia II 5, Asia II 6, Asia II 7, Asia II 12, and Australia/Indonesia.…”
Section: Introductionmentioning
confidence: 99%